EFFECT OF MOUNT AGUNG ERUPTION ON NUTRIENT CONSUMPTION AND DIGESTIBILITY (In Vitro) OF BALI CATTLE RATIONS BEFORE AND WHILE IN TALIBENG EVACUATION ZONES, SIDEMEN DISTRICT, KARANGASEM REGENCY - P. P. Y., Hendriana; Suryani, N. N.; Budiasa, I K. M. (Jurnal Peternakan Tropika, 2019)
Mount Agung eruption in August to December 2017, caused the evacuation of bali cattle to evacuation zones. This study aims to compare the quality of Bali cattle rations based on nutrient consumption, dry matter digestibility, and organic matter digestibility  Bali cattle rations given before and during in evacuation zones. The first step is a survey conducted from January to April 2018 to farmers to gather information about the botanical composition given to bali cattle before and after in evacuation zones and sampling of feed ingredients (forages and concentrates). The second step is the analysis of ration samples in the laboratory from May to June 2018. The rations are made based on observations in evacuation zones and tabulation of questionnaire results data. Variables observed were consumption of nutrient rations including dry matter (DM) kg/h/d organic matter (OM) kg/h/d, crude protein (CP) g/h/d, crude fiber (CF) g/h/d , ether extract (EE) g/h/d, and gross energy (GE) k.kal/h/d and feed digestibility including dry matter digestibility (DMD) %, and organic matter digestibility (OMD)%. The results showed that the consumption of DM, OM, CP, CF, EE, and GE rations before in evacuation zones was 6.55 kg/h/d respectively, 5.87 kg/h/d, 1,174.77 g/h/d, 1697.42 g/h/d, 443.12 g/h/d, and 26,374.82 kcal/h/d, as well as in evacuation zones, each 6.61 kg/h/d, 5.88 kg/h/d, 1082.96 g/h/d, 1769.47 g/h/d, 405.34 g/h/d, 25,072.90 kcal/h/d. DMD and OMD of Bali cattle rations before in evacuation zones were higher, but the analysis of the two rations showed different results which were not significant so it was concluded that the two types of rations were of good quality.   Keywords : consumption of nutrients, rations, digestibility, dry matter, organic matter, eruption of Mount Agung